Conservação dos quelônios amazônicos: ecologia populacional e perfil dos caçadores da espécie Podocnemis Expansa (Tartaruga–da–Amazônia) no entorno do Parque Nacional do Araguaia, Tocantins - Faria, Vailton Alves de (Universidade Federal do Tocantins, 2018)
The work seeks to contribute to the understanding of the conservation of the species of Podocnemis expansa by means of studies on reproductive ecology, the advancement of agricultural frontiers and the control, hunting and commercialization of these animals in the central region of the Araguaia Bananal Ecological Corridor in the State of Tocantins. The research presents a methodological approach divided into four distinct stages. Initially, it seeks to present and analyze the projections of the agricultural production of the municipalities of Caseara, Cristalândia, Formoso do Araguaia, Confusion Lagoon, Marianópolis and Pium with the number of females of species of P. expansa species nesting on the beaches of the Javaés river during the period (PQA) between 1985 and 2010. The data of agricultural production were analyzed for the historical series from 1990 to 2015, through the number of heads of cattle and area planted with temporary crops and crops all the municipalities mentioned. For the data analysis and prediction, the Box-Jenkins (1976) SelfCorrelated Integrated Average Averages model was used. Next, the objective was to evaluate the socioenvironmental profile of the people who use and / or commercialize these animals from the seizure reports and semi-structured interviews. In all, 93 infraction notices were registered, with 589 animals recaptured and returned to nature, of which more than 80% belong to the species P. expansa. The offenders assessed in the actions of inspection are essentially as low-income people, with little or no schooling and age ranging from 21 to 75, all males. In the interviews, 88.34% reported consuming the animals, and 51.45% preferred P. expansa, 30.09% P. unifilis, 6.70% consumed Chelonoidis sp and only 11.76% did not consume, of this total, 60.19% stated that they did not consume eggs. 61.16% stated that the main capture period is from August to December and that the Indians are the main responsible for capture and commercialization, being pointed out by 49.51% of the interviewees. For the great majority, 67%, there is no inspection in the region and, even without inspection, the amount of animals in the wild is reasonable. For 41.74%, sustainable management through quotas would be the best alternative for the preservation and conservation of species. In the third stage, the geomorphological aspects of the expansa nesting areas between 1985 and 2010 were evaluated in five beaches of the Javaés river in the central region of the Araguaia National Park on Bananal Island. The density of the nests along the beaches showed a preference of these animals for environments that have distinct geomorphological characteristics, either in relation to the physical dimensions, elevation of the sandbank or variations in the level of water in the river. In the fourth and last stage of the research, the objective was to evaluate the reproductive pattern of P. expansa females in a natural environment. The size of the females was estimated from the traces left by them during ambulation and / or shortly after laying. The results show that larger females have litters with more eggs, larger pups and larger body mass.